Activation of AMPA Receptors in the Lateral Habenula Produces Anxiolytic Effects in a Rat Model of Parkinson’s Disease - Zhang, Jin; Wang, Xiaobing; Bernardi, Rick E.; Ju, Jun; Wei, Shoupeng; Gong, Zhiting (Frontiers in Pharmacology, 2022)
Background Anxiety is a common symptom in Parkinson’s disease (PD), however, the mechanisms underlying PD-mediated anxiety remain elusive. The lateral habenula (LHb) is a critical brain region that influences the activity of the monoaminergic system in the midbrain and consequently modulates anxiety. Most neurons in the LHb express AMPA receptors. We performed the unilateral 6-hydroxydopamine (6-OHDA) lesion of the substantia nigra pars compacta (SNc) to establish the PD model for the pharmacological intervention of AMPA receptors. Methods The AMPA receptor agonist (S)-AMPA and antagonist NBQX were microinjected into the LHb to examine whether anxiety-like behaviors were altered in sham-operated rats and SNc-lesioned rats as measured using the open-field test (OPT) and elevated plus maze (EPM). Furthermore, dopamine (DA) and 5-hydroxytryptamine (5-HT) levels in the basolateral amygdala (BLA) were measured using in vivo microdialysis immediately following the injections of (S)-AMPA and NBQX into the LHb. Results Activation of LHb AMPA receptors by (S)-AMPA produced anxiolytic-like behaviors and increased extracellular DA and 5-HT in the BLA. Conversely, NBQX induced anxiety-like effects and decreased extracellular DA and 5-HT in the BLA. Conclusions These findings suggest that the effects of AMPA receptors in the LHb on anxiety-like behaviors likely involve extracellular levels of DA and 5-HT in the BLA. The present results may have implications for improving our understanding of the neuropathology and/or treatment of PD.